Collapse behavior of thin-walled corrugated tapered tubes under oblique impact. (January 2018) - Alkhatib, Sami E.; Tarlochan, Faris; Hashem, Ahmed; Sassi, Sadok
Abstract: Thin-walled structures are used in safety applications such as automotive vehicles and locomotives because of their efficient energy absorption, light weight, and reduced manufacturing cost. The performance of these structures is inhibited under oblique loading conditions. This paper numerically studies the crushing behavior and performance of corrugated tapered tubes (CTTs) as potential efficient thin-walled structures under oblique loading conditions. The proposed CTT design is impacted under 7 different loading angles with a striker mass of 275 kg and 15 m/s velocity. The material assigned to the proposed design structure is AA6060 aluminum alloy. The effect of loading angles on various performance indicators, such as the initial peak force (PF), mean crushing force (MF), energy absorption (EA) and specific energy absorption (SEA) was studied. It was found that increasing the impact angles lead to a reduction in performance, and a reduction of around 54% in EA and SEA was observed when the impact angle increased from 0° to 40°. Moreover, the effect of the geometric parameters on the performance indicators was also investigated. In addition, global bending was found to develop at higher impact angles for CTTs of 80° tapered angles. Finally, it was found that some CTTs can achieve higher SEA relative to their tapered conventional counterparts. Highlights: A novel corrugated tapered tubular structure was proposed as an energy absorber for oblique loading conditions. Corrugation reduces magnitude of the dynamic crushing forces. The transition to global bending depends mainly on the tapered angle. Corrugated tapered tubes (CTTs) can achieve higher SEA than conventional tapered tubes.